TEKNIK CLOZE PROCEDURE MENINGKATKAN KETRAMPILAN MENULIS CAPTION SISWA KELAS XII MIPA-4 SMA NEGERI 3 PURWOREJO - SUHARYONO SUHARYONO (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
This research is motivated by the low level of understanding of the Caption learning concept. The research subjects were students of class XII MIPA-4 SMA Negeri 3 Purworejo, totaling 35 students consisting of 26 female students and 9 male students. The KKM value for English subjects that has been determined is 70. The results show that in the initial state (pre-cycle) an average score of 63.6 is obtained and the percentage of classical completeness achieved is 31% or 14 of 35 students completed while 21 students or 69 The other % have not achieved complete learning. These results indicate that the initial state (pre-cycle) indicators of success have not been achieved. Because students who reach the KKM are only 31%. The highest score is 78.00 and the lowest score is 48 and classical completeness is 31%, so this is still far below the percentage of indicators that have been set, namely the learning outcomes of 80% of students reaching the KKM. To overcome this problem, the author uses the Cloze Procedure technique to improve student learning outcomes in learning English Caption material for class XII MIPA-4 semester 1 SMA Negeri 3 Purworejo students in the 2021/2022 academic year. This study uses a test instrument. The data obtained were analyzed descriptively comparatively to see the students' comprehension ability in writing captions. The results showed an increase in learning outcomes from the original 31% with an average value of 63.6 in the initial test conditions to 80% with an average value of 72.1 in the first cycle and in the second (final) cycle it increased to 94% with a an average of 80.1 after the teacher used the Cloze Procedure technique. Based on the results of this observation, there was an increase in the positive direction up by 49% from 31% in the initial conditions to 80% in the first cycle conditions and in the second cycle it increased by 14% from 80% in the first cycle conditions to 94% in the second cycle conditions. So it can be concluded that the use of the Cloze Procedure technique can improve students' understanding of English learning Caption material. ABSTRAKPenelitian ini diatar belakangi rendahnya tingkat pemahaman konsep pembelajaran Caption. Subjek penelitian adalah siswa kelas XII MIPA-4 SMA Negeri 3 Purworejo yang berjumlah 35 siswa terdiri atas 26 siswa perempuan dan 9 siswa laki-laki. Nilai KKM mata pelajaran Bahasa Inggris yang telah ditetapkan adalah 70. Hasil penelitian menunjukkan bahwa pada keadaan awal (prasiklus) diperoleh nilai rata-rata sebesar 63,6 dan persentase ketuntasan klasikal yang tercapai 31% atau 14 dari 35 siswa tuntas sedangkan 21 siswa atau 69% lainya belum mencapai ketuntasan belajar. Hasil ini menunjukkan bahwa keadaan awal (prasiklus) indikator keberhasilan belum tercapai. Karena siswa yang mencapai KKM hanya 31%. Nilai tertinggi 78,00 dan nilai terendah 48 dan ketuntasan klasikal 31%, maka ini masih jauh di bawah presentase indikator yang telah ditetapkan yaitu hasil belajar 80% siswa mencapai KKM . Untuk mengatasi permasalahan ini penulis menggunakan teknik Cloze Procedure guna meningkatkan hasil belajar siswa dalam pembelajaran bahasa Inggris materi Caption pada siswa kelas XII MIPA-4 semester 1 SMA Negeri 3 Purworejo tahun pelajaran 2021/2022. Penelitian ini menggunakan instrumen test. Data yang diperoleh dianalisis secara deskriptif komparatif untuk melihat kemampuan pemahaman siswa menulis Caption. Hasil penelitian menunjukkan adanya peningkatan hasil belajar semula 31% dengan nilai rata-rata 63,6 pada kondisi test awal menjadi 80% dengan nilai rata-rata 72,1 pada kondisi siklus I dan pada siklus II (akhir)naik menjadi 94% dengan nilai rata-rata 80,1 setelah guru menggunakan teknik Cloze Procedure . Berdasarkan hasil observasi hal ini terjadi peningkatan kearah positif naik sebesar 49% dari 31% pada kondisi awal menjadi 80% pada kondisi siklus I dan pada siklus II naik sebesar 14% dari 80% pada kondisi siklus I menjadi 94% pada kondisi siklus II. Sehingga dapat disimpulkan bahwa penggunaan teknik Cloze Procedure dapat meningkatkan pemahaman siswa terhadap pembelajaran bahasa Inggris materi Caption.